(untitled) (Revista Contexto & Saúde, 2022)
Motor development is not part of the diagnostic criteria for people with Autistic Spectrum Disorder, but it must be considered in the assessment and intervention process of ASD children. Objectives: To carry out translation and transcultural adaptation to Portuguese / Brazil version of the Movement Assessment Battery for Children-2 (MABC-2) for the 7-10 year age group and test the version translated into children with ASD. Method: The study was applied to 41 boys with ASD and correlated with Raven’s Colored Progressive Matrices test (CPM). Results and Discussion: It was observed that the correlations with the standard scores between the domains assessed by MABC-2 and the CPM results showed to be median for MD (r = 0.454, p = 0.012) and B (r = 0.324, p = 0.081) and small for A&C (r = 0.170, p = 0.368). By the traffic light system, 83% of those evaluated were classified in the red zone, with significant motor deficits. Conclusion: Correlation tests showed that the degree of intelligence seems to influence motor performance. The relevance of studies and assessments about motor area for ASD children is considered, minimizing the factors that may interfere with the motor tasks performance.